LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN PADA STRUKTUR MODAL - Maria Purwantini; Ronowati Tjandra (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This research aims to explore the influence of liquidity, profitability and company size on the capital structure of mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The variables used in this research consist of current ratio, return on assets, size and capital structure. The population of this research is mining companies listed on the BEI for the 2017-2021 period. The sampling technique in this research used purposive sampling and a sample of 21 mining companies was obtained. The analysis techniques used are descriptive analysis, classical assumption tests (including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests) and hypothesis tests. Hypothesis testing uses multiple linear regression analysis. The results of this research indicate that liquidity, profitability and company size have no effect on capital structure. Implications for other researchers who are interested in studying similar things or even developing them. Use a longer duration or one that is more up to date to provide better results.